Time preference and investment expenditure - Hülsmann, Jörg Guido (REVISTA PROCESOS DE MERCADO, 2008)
This paper offers a critique of the Austrian theory according to which social time preference determines the proportion between aggregate consumption and aggregate saving, and therefore also the volume of total investment expenditure. We argue that there is no such necessary relationship between the (pure) interest rate and the volume of aggregate investment. Then we discuss the implications of our thesis for growth theory and business-cycle theory, stressing in particular the need to distinguish between two types of growth and two corresponding types of inter-temporal misallocation. Key words: Time Preference, Time Market, Investment Expenditure, Growth Types, Inter-Temporal Mis-allocation, Austrian Business-Cycle Theory, Austrian Macroeconomics. JEL classification: B53, D01, D40, D92, E22, E32, E43. The purpose of this paper is to offer a critique of the theory according to which social time preference determines the proportion between aggregate consumption and aggregate saving, and therefore also the volume of total investment expenditure. This theory is held by virtually all Austrian economists past and present. We will first present it based on Rothbard’s Man, Economy, and State, where it is stated in the clearest and most detailed form. Then we will examine its shortcomings and discuss some implications of our findings.